Bioavailable fluoride in calcium-containing dentifrices - Shen, Peiyan (Sci Rep, 2021)
Calcium added to dentifrices can complex with fluoride ions to reduce intra-oral bioavailability and therefore efficacy in preventing dental caries. Six commercially available dentifrices containing different types of calcium and fluoride were analyzed for total and bioavailable fluoride levels by adding 10 g of dentifrice to 30 mL of distilled deionized water and mixing vigorously for 1 min to simulate toothbrushing. One milliliter of the dentifrice/water slurry was immediately centrifuged and the supernatant removed for bioavailable fluoride analysis and the mixed slurry prior to centrifugation used for total fluoride analysis using a modified microdiffusion method. The concentration of fluoride was determined using a fluoride ion-selective electrode calibrated with internal fluoride standards. All the dentifrices had similar total fluoride concentrations to those indicated on their labels (94% to 105%). However, only one dentifrice that contained calcium in the form of casein phosphopeptide amorphous calcium phosphate (CPP-ACP) had almost 100% (97%) of fluoride in bioavailable form. The other dentifrices contained calcium carbonate and they exhibited significantly (p < 0.001) lower bioavailable fluoride levels (27% to 61%), through the generation of poorly soluble fluoride phases. The saliva biomimetic CPP, as CPP-ACP, in a dentifrice stabilised calcium and fluoride ions to maintain fluoride’s bioavailability.